Penguatan Kemampuan Refleksi Guru Terkait Pembelajaran Daring di Masa Pandemi Covid-19 - Puput Amarta; Dyan Putri Ayu (Social Science Academic, 2023)
Since Covid-19 has spread more and more, the government has made many policies so that people can adjust to the natural conditions that are currently happening. One of the policies in the world of education is the implementation of an online system in the teaching and learning process. This is a student complaint because the tasks given are more. As well as the large number of educators and also teaching participants who feel they are not ready for this virus as if forcing everyone to be ready with technological developments. This study aims to find out how the influence of online methods and their effectiveness in the teaching and learning system at SDN 1 Kesugihan, Pulung District. This research is a qualitative research using a case study research design, and Participatory Rural Appraisal (PRA) approach. The results of the study stated that several positive impacts were obtained when learning online, especially felt by parents of students. However, there are also several obstacles because the online system is a new thing for most students, teachers, and parents whose children attend SDN 1 Kesugihan, Pulung District.